ANALISIS PENGGUNAAN MODEL TEAMS GAMES TOURNAMENT DALAM MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Risa Nursyamsiah; Lutfi Asyari; Mohamad Ramdan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of the Teams Games Tournament (TGT) learning model in improving elementary school students’ learning outcomes and to identify the supporting and inhibiting factors in its implementation during the learning process. This study employed a qualitative method with a literature review approach. The data were obtained from various relevant sources such as books, scientific journals, research articles, and academic documents related to the Teams Games Tournament learning model and elementary school students’ learning outcomes. Data collection techniques were conducted through documentation studies and content analysis, while data analysis was carried out by collecting, reviewing, comparing, and classifying information based on the research themes. The results showed that the use of the Teams Games Tournament model was able to create an active, interactive, and enjoyable learning atmosphere, thereby improving students’ motivation and learning outcomes in elementary schools. This model also improved students’ cooperation, responsibility, communication, and participation during the learning process. In addition, the implementation of the TGT model helped students understand the material more easily because the learning process was packaged through group discussions, educational games, and academic tournaments. Supporting factors in implementing the TGT model included teacher creativity, the use of attractive learning media, and active student participation. Meanwhile, the obstacles found included differences in students’ abilities, limited learning time, and teachers’ readiness in implementing innovative learning models. Therefore, the Teams Games Tournament model can be used as an effective alternative learning model to improve elementary school students’ learning outcomes.